MANFAAT HASIL BELAJAR KONTRUKSI POLA BUSANA PADA PEMBUATAN POLA BUSANA KERJA WANITA - Latifah Latifah; Katiah Katiah (Fesyen Perspektif, 2016)
Competence making  women’s fashion can be used as a benchmark as students readiness to plunge into working world through industry work  practice  program. The  research  used  survey method. The technique of collecting data using questionnaires. The  population in this research is class XI Students of  SMK Negri 6 Garut . The sample used is total sample amount to 25 students.. This research disclosed  that  most of the students know the benefits of  making  women’s fashion learning result  in terms of  making women’s fashion, women’s fashion sewing basic competencies, completion of women’s fashion with hand stitching and doing pressing the manufacture of  women’s fashion. The conclusion of this research  indicate that  students are able to take advantage of  making women’s fashion learning result become the readiness to follow the industry work practice.